Digital Literacy Level of Senior High School Students in Bandung - Lidia Gustina Tampubolon; Nandi; Ahmad Yani (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
In response to the rapid changes in society especially in education and technology areas, the need for 21st-century skills, such as digital literacy has also increased. For instance, digital literacy-based learning has been applied in geography for a long time through the use of electronic devices in the learning process. However, to use knowledge and skills related to technology effectively in the learning process, students are also required to have critical thinking skills and be proficient in evaluating information provided in digital media. This study aims to analyze digital literacy level of senior high students in Bandung. The research method used is quantitative approach by distributing multiple-choice questionnaire to 83 senior high school students. The results of the test showed the students have a high digital literacy in terms of ICT/digital/computer literacy, information literacy, communication and collaborations skills, and creativity. While in indicators such as media literacy, learning to learn skills, and citizenship still require improvement.